2007
DOI: 10.1051/forest:2006105
|View full text |Cite
|
Sign up to set email alerts
|

Radial variation of wood density components and ring width in cork oak trees

Abstract: -The radial variation of ring width and wood density was studied in cork oaks (Quercus suber) using microdensitometry. The observations were made in young never debarked cork oaks (30-40 years of age) and in mature trees under cork production (37-60 years of age). The cork oak wood is very dense (mean ring density 0.86 g.cm −3 , between 0.79 g.cm −3 and 0.97 g.cm −3 ) with a small intra-ring variability (mean earlywood density 0.80 g.cm −3 and latewood density 0.90 g.cm −3 ). The density components decreased f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 31 publications
3
35
1
2
Order By: Relevance
“…Although a positive correlation between the density and width of annual rings for ring-porous tree species, or between density and proportion of latewood, is generally assumed (Kollmann 1951;Tsoumis 1991), there are also studies in which this has not been confirmed, which suggests that the issue is much more complicated and that the structure of latewood also plays a role. Knapic et al (2007) found no relationship between the width of the annual rings and the proportion of latewood. Bergès et al (2008) reported a weak or insignificant correlation between density and the width of annual rings and proportion of latewood.…”
Section: Annual Ring Width and Its Correlation With Wood Density And mentioning
confidence: 72%
See 1 more Smart Citation
“…Although a positive correlation between the density and width of annual rings for ring-porous tree species, or between density and proportion of latewood, is generally assumed (Kollmann 1951;Tsoumis 1991), there are also studies in which this has not been confirmed, which suggests that the issue is much more complicated and that the structure of latewood also plays a role. Knapic et al (2007) found no relationship between the width of the annual rings and the proportion of latewood. Bergès et al (2008) reported a weak or insignificant correlation between density and the width of annual rings and proportion of latewood.…”
Section: Annual Ring Width and Its Correlation With Wood Density And mentioning
confidence: 72%
“…Adamopoulos et al (2007) did not find a significant difference in the wood density between the central and peripheral parts of the trunk. Most studies have reported the opposite trend, i.e., a decrease in density in the direction from the pith toward the bark; for example, Vavrčík and Gryc (2012) reported such a density distribution for Q. robur, Ayobi et al (2011) for Q. castaneaefolia, and Knapic et al (2007) for Q. suber. Panshin and Zeeuw (1980) stated that there was very little consistency and no overall dominance of a single pattern in hardwood tree species for density fluctuation with respect to the height of the trunk.…”
Section: Effect Of Position On Wood Density In Q Rubra and Q Roburmentioning
confidence: 99%
“…80 years. Regarding wood density, Q. faginea mature trees showed high values that are similar to other oaks such as Q. suber (0.75 to 1.07 g/cm 3 ) (Knapič et al, 2007(Knapič et al, , 2008 and Q. cerris (0.96 g/cm 3 ) (Dilem, 1995). Despite this similarity, Q. faginea wood density values are higher than those found for the currently highly valued oaks such as Q. petraea (0.66 -0.83 g/cm 3 ) (Bergès et al, 2008), Q. rubra (0.54 -0.76 g/cm 3 ), and Q. robur (0.52 -0.63 g/cm 3 ) (Nepveu, 1984;Genet et al, 2012).…”
Section: Discussionmentioning
confidence: 89%
“…Thus, hardwoods are generally more sensitive to thermal degradation than softwoods, while woods with high densities seem to be more sensitive to thermal degradation than less dense woods ). Relative to intra-species differences, wood quality of European oak is reported to be deeply influenced by ring width depending on ecological factors, soil quality, forest management, tree age, and genetics (Bouriaud et al 2004;Zhang et al 1993;Knapic et al 2007;Bergès et al 2008). In this context, wood density is often used as a functional trait in tree ecology to evaluate wood quality.…”
Section: Introductionmentioning
confidence: 99%